1992
DOI: 10.1111/j.1365-2044.1992.tb02133.x
|View full text |Cite
|
Sign up to set email alerts
|

Central venous access in children via the external jugular vein

Abstract: SummarySixty-two children undergoing cardiac surgery were surveyed for the presence of external jugular veins. When present, these were used as a route for central venous catheterisation using a 'J' wire Seldinger technique. Only 54% of attempted insertions were successful but the results support greater efJacy in older children. Key wordsVeins; jugular, external, cannulationThe external jugular vein (EJV) provides a safe and reliable route for central venous access in adults especially where a 'J' wire techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 5 publications
1
3
1
1
Order By: Relevance
“…The overall success rate found in the present study (100%) corroborates other published studies (59-100%), which characterize the pediatric application of the Seldinger technique as safe and with low morbidity (5.8%) [11][12][13][14][15][16][17][18][19][20]. The profile of this case series does not differ from other studies [1,16,18,21].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The overall success rate found in the present study (100%) corroborates other published studies (59-100%), which characterize the pediatric application of the Seldinger technique as safe and with low morbidity (5.8%) [11][12][13][14][15][16][17][18][19][20]. The profile of this case series does not differ from other studies [1,16,18,21].…”
Section: Discussionsupporting
confidence: 94%
“…The mean age of 4 years is similar to the majority of reports in the literature. Although age and weight were reported previously as factors associated with lower rates of success by some authors [7,13,17,19,20], these factors did not influence our global success rate. However, we observed that in children with a lower body weight a change of puncture site for CVC was statistically significant (P<0.05).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…All articles regarding this subject report use of peripherally inserted central catheters or double-lumen short-term catheters for catheterization of the external jugular vein [5][6][7][8]. In almost 25% of our patients, a long-term catheter was inserted, thus presenting a further option to avoid major risks in selected patients.…”
Section: Discussionmentioning
confidence: 96%
“…The first report in children was in 1982, but the authors reported only a 59% success rate [6]. Taylor et al [7] reported a 54% success rate, suggesting that there might be a higher efficacy in older children. A recent study reported a 72.5% success rate of central venous catheterization through the external jugular vein and claimed it to be the highest one ever reported in children.…”
Section: Discussionmentioning
confidence: 97%